2019
DOI: 10.1108/mmms-08-2019-0147
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of fully wet longitudinal porous fin with temperature-dependent thermal conductivity, surface emissivity and heat transfer coefficient

Abstract: Purpose The purpose of this paper is to study the thermal behaviour of a fully wet porous fin of longitudinal profile. The significance of radiative and convective heat transfer has been scrutinised along with the simultaneous variation of surface emissivity, heat transfer coefficient and thermal conductivity with temperature. The emissivity of the surface and the thermal conductivity are considered as linear functions of the local temperature between fin and the ambient. Darcy’s model was considered to formul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The thermal conductivity k(T) $k(T)$ and convective heat transfer coefficient h(T) $h(T)$ of the fin are given by 8,23 k(T)=ka(1+α(TTa)), $k(T)={k}_{a}(1+\alpha (T-{T}_{a})),$ h(T)=haTTaTbTap=hDCpLe23, $h(T)={h}_{a}{\left(\frac{T-{T}_{a}}{{T}_{b}-{T}_{a}}\right)}^{p}={h}_{D}{C}_{p}L{e}^{\frac{2}{3}},$where ka ${k}_{a}$ is the thermal conductivity at temperature Ta ${T}_{a}$, α $\alpha $ is the measure of thermal conductivity variation with temperature, ha ${h}_{a}$ is the heat transfer coefficient at temperature Ta ${T}_{a}$, hD ${h}_{D}$ is the uniform mass transfer coefficient, italicLe ${Le}$ is the Lewis number, Cp ${C}_{p}$ is the specific heat of the ambient fluid, and p $p$ is the exponential index.…”
Section: Modeling Of the Physical Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal conductivity k(T) $k(T)$ and convective heat transfer coefficient h(T) $h(T)$ of the fin are given by 8,23 k(T)=ka(1+α(TTa)), $k(T)={k}_{a}(1+\alpha (T-{T}_{a})),$ h(T)=haTTaTbTap=hDCpLe23, $h(T)={h}_{a}{\left(\frac{T-{T}_{a}}{{T}_{b}-{T}_{a}}\right)}^{p}={h}_{D}{C}_{p}L{e}^{\frac{2}{3}},$where ka ${k}_{a}$ is the thermal conductivity at temperature Ta ${T}_{a}$, α $\alpha $ is the measure of thermal conductivity variation with temperature, ha ${h}_{a}$ is the heat transfer coefficient at temperature Ta ${T}_{a}$, hD ${h}_{D}$ is the uniform mass transfer coefficient, italicLe ${Le}$ is the Lewis number, Cp ${C}_{p}$ is the specific heat of the ambient fluid, and p $p$ is the exponential index.…”
Section: Modeling Of the Physical Problemmentioning
confidence: 99%
“…The transient response of distinct profiles of the longitudinal fin was investigated by Pasha et al 7 by employing the semianalytical method of differential transformation. Sowmya et al 8 scrutinized the porous fin problem in the presence of fully wet conditions. It has been concluded that the porosity and wet nature of the fin enhance the rate of exchange of heat.…”
Section: Introductionmentioning
confidence: 99%
“…The direct technique used in the study was based on the series expansion of temperature in the mounted surface area, which required no numerical technique to find the temperature. Sowmya et al (2019) studied the performance of a fully wetted longitudinal porous fin. The conductivity and emissivity were taken as a linear function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Heat transmission is the phenomenon used to explain heat transfer from higher temperatures toward lower concentrations (Gireesha and Sowmya 2020). In recent years, the process of heat transfer has emerged as the most important subject in the field of thermal engineering due to the prediction Responsible Editor: Mehmet Polat Saka of heat exchanger in variety of circumstances including solar collector, gas turbines, radiators in cars, and energy production (Alkam and Al-Nimr 1999;Deshamukhya et al 2018;Sowmya et al 2019;Khan et al 2021d). The heat exchangers or extended surfaces are an integral part of any device that generates heat during its working process.…”
Section: Introductionmentioning
confidence: 99%